Effect of sodium bicarbonate on cardiovascular outcome and mortality in patients with advanced chronic kidney disease - Cheng, Ya-Lien; Huang, Shu-Chun; Ho, Ming-Yun; Li, Yan-Rong; Yen, Chieh-Li; Chen, Kuan-Hsing; Sun, Wei-Chiao; Fan, Pei-Yi; Chen, Jung-Sheng; Lin, Chihung; Hsiao, Ching-Chung (Frontiers in Pharmacology, 2023)
Background: Metabolic acidosis is common in patients with chronic kidney disease (CKD). Oral sodium bicarbonate is commonly used to treat metabolic acidosis and prevent the progression of CKD. However, there is limited information about the effect of sodium bicarbonate on major adverse cardiovascular events (MACE) and mortality in patients with pre-dialysis advanced CKD Method: The cohort study was conducted using data from the Chang Gung Research Database, a multi-institutional electronic medical record database in Taiwan. A cohort of 25599 patients with CKD stage V were identified between January 1, 2001 to December 31, 2019. The exposure was defined as receiving sodium bicarbonate or not. The primary outcomes were dialysis initiation, major adverse cardiovascular events (MACE) (myocardial infarction, heart failure, stroke), and all-cause mortality. Stabilized inverse probability of treatment weighting was used to balance baseline covariates. We compared risks of dialysis, MACE and mortality between groups using Cox proportional hazards models. In addition, we conducted an analysis using Fine and Gray sub-distribution hazard model that considered death as competing risk. Result: Among 25599 patients with CKD stage V, 5084 patients (19.9%) were sodium bicarbonate users while 20515 (80.1%) were sodium bicarbonate non-users. The groups had similar risk of dialysis initiation (HR, 0.98; 95% CI 0.95-1.02, p<0.379). However, taking sodium bicarbonate was associated with a significantly lower risks of MACE (HR, 0.95; 95% CI 0.92 -0.98, p<0.001) and hospitalizations for acute pulmonary edema (HR, 0.92; 95% CI 0.88 -0.96, p<0.001) compared with non-users. The mortality risks were significantly lower in sodium bicarbonate users compared with sodium bicarbonate non-users (HR, 0.75; 95% CI 0.74 -0.77, p<0.001) Conclusion: The cohort study found that in real world practice, among patients with advanced CKD stage V, use of sodium bicarbonate was associated with similar risk of dialysis compared with non-users, Nonetheless, use of sodium bicarbonate was associated with significantly lower rate of MACE and mortality. The study results reinforced the benefits of sodium bicarbonate therapy in the expanding CKD population. Further prospective studies are needed to confirm these findings.